Perbedaan Kompetensi Sosial Siswa Boarding School dan Siswa Sekolah Umum Reguler - Tesi Hermaleni; Mudjiran Mudjiran (Universitas Negeri Padang, 2016)
Abstract: The difference between boarding school students and regular students. This research is motivated by social competence as one of the important aspects of the adolescent social development and also to strengthen their identity and their role in society. This study was a comparative. Sample was 128 people; MAKN Koto Baru 64 students and 64 students of MAN 2 Bukittinggi using Proportional Random Sampling technique. The research instrument used in data collection is the scale of social competence. Hypothesis testing is done by using T-test techniques analysis. The results show there are differences in the students' social competence Boarding School and a regular public school students with p equal to 0.049.Keywords: social competence, boarding school, regular public schools. Abstrak : Perbedaan kompetensi sosial siswa boarding school dan siswa sekolah umum reguler. Penelitian ini dilatarbelakangi oleh kompetensi sosial sebagai salah satu aspek penting dalam perkembangan sosial remaja selain itu juga untuk memperkukuh identitas diri serta perannya dalam masyarakat. Desain penelitian ini adalah komparatif. Sampel penelitian sebanyak 128 orang ; 64 siswa MAKN Koto Baru dan 64 siswa MAN 2 Bukittinggi dengan menggunakan teknik Proportional Random Sampling. Instrumen penelitian yang digunakan dalam pengumpulan data adalah skala kompetensi sosial. Uji hipotesis dilakukan dengan menggunakan teknik analisis uji beda T-test. Hasil uji hipotesis menunjukkan terdapat perbedaan kompetensi sosial siswa Boarding School dan siswa sekolah umum reguler dengan t hitung 1, 988 dan p sebesar 0,049.Kata Kunci: Kompetensi sosial, boarding school, sekolah umum regular.